Prediagnostic Serum Vitamin D Levels and the Risk of Crohn's Disease and Ulcerative Colitis in European Populations: A Nested Case-Control Study. Issue 3 (16th February 2018) - Opstelten, Jorrit L; Chan, Simon S M; Hart, Andrew R; van Schaik, Fiona D M; Siersema, Peter D; Lentjes, Eef G W M; Khaw, Kay-Tee; Luben, Robert; Key, Timothy J; Boeing, Heiner; Bergmann, Manuela M; Overvad, Kim; et al.
Abstract: Background: A low vitamin D status has been put forward as a potential risk factor for the development of inflammatory bowel disease (IBD). This study investigated the association between prediagnostic circulating vitamin D concentrations and dietary intakes of vitamin D, and the risk of Crohn's disease (CD) and ulcerative colitis (UC). Methods: Among 359, 728 participants of the European Prospective Investigation into Cancer and Nutrition cohort, individuals who developed CD or UC after enrollment were identified. Each case was matched with2 controls by center, gender, age, date of recruitment, and follow-up time. At cohort entry, blood samples were collected and dietary vitamin D intakes were obtained from validated food frequency questionnaires. Serum 25-hydroxyvitamin D levels were measured using liquid chromatography-tandem mass spectrometry. Conditional logistic regression was performed to determine the odds of CD and UC. Results: Seventy-two participants developed CD and 169 participants developed UC after a median follow-up of 4.7 and 4.1 years, respectively. Compared with the lowest quartile, no associations with the 3 higher quartiles of vitamin D concentrations were observed for CD (p trend = 0.34) or UC (p trend = 0.66). Similarly, no associations were detected when serum vitamin D levels were analyzed as a continuous variable. Dietary vitamin D intakes were not associated with CD (p trend = 0.39) or UC (p trend = 0.83). Conclusions: Vitamin D status was not associated with the development of CD or UC. This does not suggest a major role for vitamin D deficiency in the etiology of IBD, although larger studies are needed to confirm these findings.